Economic Growth Analysis Using Dynamic Panel Data Regression with GMM Arellano-Bond Estimation - Al Azhar, Sarah Ardina (Integrated Journal of Business and Economics (IJBE), 2025)
This research highlights the important role of economic growth in improving society's welfare. This study evaluates the influence of the Human Development Index, Foreign Direct Investment, Poverty Levels and Income Inequality on economic growth in Indonesia in the 2014-2023 period. By applying the Generalized Method of Moments (GMM) method through the FD-GMM and SYS-GMM approaches, the analysis results show that the Human Development Index and Income Inequality have a positive and significant impact on economic growth. Meanwhile, Foreign Direct Investment and Poverty Levels do not show a significant influence. This research aims to examine the short and long term relationship between these variables and economic growth in Indonesia. It is hoped that the findings in this study can become a reference in formulating policies to encourage more optimal economic growth.Keywords: Macroeconomics, Economic Growth, General Method of Moment, Short-Term,Long-Term